2019
DOI: 10.5194/bg-16-617-2019
|View full text |Cite
|
Sign up to set email alerts
|

Variation in brachiopod microstructure and isotope geochemistry under low-pH–ocean acidification conditions

Abstract: Abstract. In the last few decades and in the near future CO2-induced ocean acidification is potentially a big threat to marine calcite-shelled animals (e.g. brachiopods, bivalves, corals and gastropods). Despite the great number of studies focusing on the effects of acidification on shell growth, metabolism, shell dissolution and shell repair, the consequences for biomineral formation remain poorly understood. Only a few studies have addressed the impact of ocean acidification on shell microstructure and geoch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 100 publications
0
9
1
Order By: Relevance
“…; Ye et al . ) although an unpublished specimen from Huinay Station is 5 mm‐thick in section (Elizabeth Harper, pers. comm.)…”
Section: Discussionmentioning
confidence: 99%
“…; Ye et al . ) although an unpublished specimen from Huinay Station is 5 mm‐thick in section (Elizabeth Harper, pers. comm.)…”
Section: Discussionmentioning
confidence: 99%
“…Establishing a baseline can help in detecting early effects of acidification on fjords ecosystems; calcifiers organisms, such as gastropods and bivalves (e.g., Thomsen et al, 2012), and also CWCs (Turley et al, 2007) may represent valid sentinel species. Globally, brachiopods appear to be less impacted by ocean acidification (Cross et al, 2015(Cross et al, , 2016, probably thanks to compensating mechanisms (Cross et al, 2019), but microstructural changes have been observed in the shell of the Chilean fjords' species M. venosa (Ye et al, 2019). With warming and climate change seriously threatening these Chilean fjords benthic communities, it is imperative to reduce general stress levels on all organisms, and on the ecosystem itself.…”
Section: A Baseline For Further Studiesmentioning
confidence: 99%
“…Brand et al 2011). Shells of the Terebratulida and Rhynchonellida are one of the most used biogenic structural materials for paleoenvironment reconstruction as they cover almost the entire geologic record, are wide-spread in marine habitats and, most of them, secrete low-Mg calcite shells (Al-Aasm and Veizer 1982;Veizer et al 1999;Brand et al 2003Brand et al , 2011Auclair et al 2003;Parkinson et al 2005;Angiolini et al 2009;von Allmen et al 2010;Payne and Clapham, 2012;Garbelli et al, 2012Garbelli et al, , 2014Cross et al 2015;Immenhauser et al 2015;Rollion-Bard et al 2016;Ye et al 2019;Jurikova et al 2020).…”
Section: Are Thecideide Shells Reliable Archives For Environmental Reconstruction?mentioning
confidence: 99%